KOMUNIKASI MATEMATIKA DALAM PEMBELAJARAN MATEMATIKA - Hoiriyah, Diyah (Logaritma : Jurnal Ilmu-ilmu Pendidikan dan Sains, 2017)
Communication mathematics has a very strong relationship with other mathematical processes, such as problem solving, representation, reflection, reasoning and proof, and connections, where communication is needed to complete each of the other mathematical processes. The ability of students 'mathematical communication is also the foundation in building students' knowledge of mathematics both oral and written. through communication allows mathematical thinking to be observed and therefore communication facilitates the development of thinking. Even though the ability of mathematical communication is important, ironically the learning of mathematics has still not given enough attention to the development of this ability, so that mastery of mathematical competencies for students is still low. students only usually teach questions that are required to seek results but are not or are rarely asked about the origin or steps of understanding. In this connection, this paper aims to explain theoretically about mathematical communication and to present the role of learning related to reality so that students can develop mathematical communication skills.